The Fourth Attempt to Construct a Politics of Welfare Obligations - Fitzpatrick, Tony (Policy Press, 2005)
Since the 1980s there have been three main attempts to ground citizenship upon the principles of duty, obligation and responsibility: conservative, communitarian and Third Way. Each of these are reviewed below. The principal task of this article, though, is to examine the emergence of a fourth attempt which, by relating duty to equality through the principle of reciprocity, represents a synthesis of traditional social democracy with the new politics of obligation. Our focus will be upon The Civic Minimum by Stuart White since this is arguably the most cogent expression of duty-based egalitarianism to have emerged in recent years.